The Seventh Amendment, Modern Procedure, and the English Common Law - Suja A. Thomas (Washington University Law Quarterly, 2004)
This Article assumes the validity of the English common law historical test to the constitutionality analysis. It argues, however, that the underlying test, unconnected to actual principles of the common law devices, has caused the invariable constitutionalization of procedures that are increasingly used by the federal courts. This Article develops principles derived from the English common law by which modern procedures that affect the jury trial right can be reassessed. These proposed principles include that procedures permitted under the English common law should be constitutional, and that procedures proscribed under the English common law should be unconstitutional. Part I begins with an examination of the modern procedural devices and an overview of the Supreme Court jurisprudence regarding the constitutionality of the new procedures under the Seventh Amendment. Scholarship regarding the “rules of the common law” is then examined. Part II analyzes the late eighteenth-century English procedural devices used to dismiss a case before a jury heard the case. The devices in place during the trial are then explored, followed by an analysis of the procedures that surrounded the verdict. Additionally, this Part describes the procedures used after a jury rendered a verdict. Each subpart on the English procedures compares the English procedures to modern procedures and critiques the Supreme Court’s analysis of the common law devices. Finally, Part III sets forth principles derived from the English common law by which the constitutionality of modern procedures may begin to be reassessed.
Keywords: Right to trial by jury; Common law -- Great Britain; Civil procedure; Criminal procedure